Comprehensive protection of winter wheat from harmful organisms of agrocenosis in the zone of the Polissya of Ukraine - A. Bakalova; N. Gritsyuk; O. Derechа (Карантин і захист рослин)
Goal. To study influence of complex application of fungicidal, insecticidal action on the dynamics of the number of harmful organisms and fusarium root rot on winter wheat crops under the conditions of the Polissya of Ukraine.